Does traditional debt financing hurt the environment?: evidence from toxic releases - Lyu, Xiaoyi (Journal of business ethics, 2025)
The sources of financing for a firm can influence its environmental ethics. This study shows that traditional debt financing is associated with more pollution. Specifically, after issuing debt, firms tend to increase not only their total pollution level but also their pollution intensity. The debt-pollution link cannot be fully explained by the production effect. This effect is more pronounced when the firm borrows for short-term purposes, has managerial short-termism, or has more risk-taking behavior. The environmental awareness of the public can weaken the debt effect. Our findings support the notion that traditional debt financing can exacerbate short-termism in firm operations, leading to a sacrifice of long-term investments that may yield future benefits. Our study suggests that green financing, such as green bonds or green loans, could help improve corporate ethical behavior.